The Euthanasia Debate and Its Implications on The Legalization of Euthanasia in Indonesia - Chia Yee Xian (Jurnal Jaffray, 2023)
Today, an ethical issue that is controversial and much debated is the practice of euthanasia. The ethical debate on euthanasia is basically about competing moral visions and values. The research method used in this study is qualitative. Information is collected from publications such as books and journals. The advocates for the legalisation of euthanasia based their reasons on compassion and individual autonomy. They argue that euthanasia is right because it removes human suffering. Everyone has the right to determine how to die, concerning when and how. They believe that certain lives, such as people in a persistent vegetative state, are not just worth living. Those who oppose euthanasia say it is morally wrong to kill helpless people, even at their request. Christians who oppose euthanasia base their arguments on the sanctity of life. A person’s freedom to decide on euthanasia should follow a structure of healthy moral values. Another key consideration in the debate is the slippery slope argument. Currently, euthanasia is prohibited in Indonesia, as stated in Article 344 of the Indonesian Criminal Code. As more countries legalise euthanasia, the writer believes that the call for legalising euthanasia in Indonesia will be intensified. We need to be better informed because law, medicine, beliefs and reason intersect in the euthanasia debate. The writer will give an overall view of the contemporary euthanasia debate from a Christian perspective.